Obesity As a Common Denominator in Breast Cancer and Cardiovascular Disease. - Rygiel, Katarzyna (Cambridge Scholars Publishing, 2019)
Obesity is widely regarded as a shared, modifiable risk factor of both breast cancer (BC) and cardiovascular disease (CVD). Human epidermal growth factor receptor 2 (HER2)-positive BC displays very aggressive behavior, and can be effectively treated with targeted therapies and chemotherapy regimens, though such treatments can induce cardiotoxicity. While the main research efforts are appropriately focused on the management of BC and heart failure (HF), obesity and its metabolic consequences, which are often linked with both these conditions, often remain unaddressed. This book combines a very p.